2017
DOI: 10.1038/srep46287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Treatment of Magnetic Nanoparticles Driven by Extremely Low Frequency Magnetic Field

Abstract: Recently, magnetic nanoparticles (MNPs), which can be manipulated in the magnetic field, have received much attention in tumor therapy. Extremely low frequency magnetic field (ELMF) system can initiate MNPs vibrating and the movement of MNPs inside of cells can be controlled by adjusting the frequency and intensity of ELMF towards irreversible cell damages. In this study, we investigated the detrimental effects on tumor cells with MNPs under various ELMF exposure conditions. An in-house built ELMF system was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
5
22
3
Order By: Relevance
“…Although particles with a shape anisotropy are preferable to transfer a mechanical action on cells, several studies have observed a lethal effect on cancer cells by TMMEP using spherical particles. 43,44,46,[49][50][51] It should be noted that such spherical particles may however form small chains due to their magnetostatic interactions in an applied magnetic eld, and thus act as a unique elongated particle. The spherical particles used in TMMEP were mainly commercially available SPIONs fabricated by chemical routes, single or in cluster, actuated by applied magnetic elds of low frequency.…”
Section: Particle Composition Concerning the Particles Compositionprmentioning
confidence: 99%
See 2 more Smart Citations
“…Although particles with a shape anisotropy are preferable to transfer a mechanical action on cells, several studies have observed a lethal effect on cancer cells by TMMEP using spherical particles. 43,44,46,[49][50][51] It should be noted that such spherical particles may however form small chains due to their magnetostatic interactions in an applied magnetic eld, and thus act as a unique elongated particle. The spherical particles used in TMMEP were mainly commercially available SPIONs fabricated by chemical routes, single or in cluster, actuated by applied magnetic elds of low frequency.…”
Section: Particle Composition Concerning the Particles Compositionprmentioning
confidence: 99%
“…Although without statistical validation, we can observe some trends based on all the in vitro studies. As shown in Table 2 (column 6), apoptosis represents, in most cases, the latest stage of the above cited cellular perturbations, 21,22,25,27,30,32,[36][37][38][39][40][41][42][43]46,[50][51][52] however with variable rates of cancer cells mortality (or viability). Some of the studies show the induction of necrosis onlysuch as necrotic membrane disruption, cell membrane leakage or cell lysis.…”
Section: Comments On the In Vitro Apoptotic Occurrence In Tmmepmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the destruction effect of moving MPs on tumor cells was demonstrated, the researchers focused their work on finding the most appropriate magnetic materials with larger mechanic torque of MPs under the variable magnetic field action. Thus, magnetite particles 6 , 7 , magnetic-vortex NiFe microdiscs prepared by magnetron sputtering followed by optical lithography 8 , 9 , ultrathin perpendicularly magnetized magnetic particles 10 , 11 , synthetic antiferromagnetic and ferrimagnetic microdiscs 12 with no magnetic remanence 13 , nanowires with various compositions obtained by electrodeposition in aluminum membranes 14 16 were studied at large for this purpose. The possibility of using STEM cells as carriers for the MPs to the tumor site, followed by the release of MPs based on magneto-mechanical actuation and destruction of cancer cells was also considered by the scientific world 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a significant increase in activity when drugs are loaded onto m-HAP nanoparticles, in contrast to the neat drug. This could be due to the remarkable ability of the carrier molecules to penetrate the cell membranes and to extend the activity [71].…”
Section: Resultsmentioning
confidence: 99%